2019
DOI: 10.5935/0103-507x.20190011
|View full text |Cite
|
Sign up to set email alerts
|

Association between site of infection and in-hospital mortality in patients with sepsis admitted to emergency departments of tertiary hospitals in Medellin, Colombia

Abstract: Objective To determine the association between the primary site of infection and in-hospital mortality as the main outcome, or the need for admission to the intensive care unit as a secondary outcome, in patients with sepsis admitted to the emergency department. Methods This was a secondary analysis of a multicenter prospective cohort. Patients included in the study were older than 18 years with a diagnosis of severe sepsis or septic shock who were admitted to the emerg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 40 publications
1
15
1
1
Order By: Relevance
“…Whether the infection site impacts clinic outcomes still remains controversial. A significant association between the site of infection and the inhospital mortality in patients with sepsis or septic shock was reported in a secondary analysis of a multicentre prospective cohort study recently [ 24 ], while several studies showed that the evidence for the conclusive statement about the role of the infection site in mortality among sepsis might not be robust for heterogeneity of study population by the present literature [ 25 , 26 ]. However, the impact of the infection site on patterns of organ failures might differ.…”
Section: Discussionmentioning
confidence: 91%
“…Whether the infection site impacts clinic outcomes still remains controversial. A significant association between the site of infection and the inhospital mortality in patients with sepsis or septic shock was reported in a secondary analysis of a multicentre prospective cohort study recently [ 24 ], while several studies showed that the evidence for the conclusive statement about the role of the infection site in mortality among sepsis might not be robust for heterogeneity of study population by the present literature [ 25 , 26 ]. However, the impact of the infection site on patterns of organ failures might differ.…”
Section: Discussionmentioning
confidence: 91%
“…10 Pulmonary infection, possibly due to a high rate of mechanical ventilation, 14 is the most common and major cause of sepsis in patients in the ICU. Caraballo et al 15 showed a significant correlation between pulmonary infection and hospital mortality in patients with sepsis (OR: 3.4, 95% CI: 2.2-5.5). Similar results were also obtained in the present study, indicating that pulmonary infections might help predict survival of patients with sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…Caraballo et al. 15 showed a significant correlation between pulmonary infection and hospital mortality in patients with sepsis (OR: 3.4, 95% CI: 2.2–5.5). Similar results were also obtained in the present study, indicating that pulmonary infections might help predict survival of patients with sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the odds of in-hospital mortality were 3.73 times greater in patients with a respiratory primary focus compared to a LUTI primary focus. It has been reported previously that respiratory infections leading to a BSI have poorer outcomes, whereas urinary tract infections have the lowest associated mortality rates [ 7 , 18 22 ]. The recent study by Inada-Kim et.…”
Section: Discussionmentioning
confidence: 99%